Inter‐ and intra‐individual variability in growth and food consumption in pikeperch, Sander lucioperca L., larvae revealed by individual rearing. (19th November 2015) - Schaefer, Fabian J; Flues, Sebastian; Meyer, Stefan; Peck, Myron A
Abstract: We examined short‐term, inter‐ and intra‐individual variability in rates of growth and food consumption in fish early life stages to gain a mechanistic understanding of why larvae in the same environments often grow at vastly different rates. We made parallel measurements of growth rate in standard length (GRSL ) and food consumption rate (C), and provide estimates of weight growth rate (GRDW ) and gross growth efficiency (GGE = 100*GRDW /C) of individually reared larvae of pikeperch, Sander lucioperca L., fed Artemia nauplii at 20°C and a salinity of 2.0 g L −1 . Within two trials, GRSL, C and GGE were obtained for 108 larvae over a maximum period of 28 days. Mean (±SD) initial size, GRSL, C and GGE were 19.49 (9.19) mm, 0.68 (0.21) mm day −1, 0.85 (0.44) mg day −1 and 36.5 (10.2)% respectively. The vast majority (91%) of the variability in growth was explained by differences in food consumption. When isolated from conspecifics for 28 days, relatively small larvae grew faster than relatively large ones, partially mitigating initial differences in size‐at‐age.